The Effect of Problem-Based Learning Model on Students Scientific Reasoning and Scientific Attitude Abilities - Yasmin, Ira; Jufri, A. Wahab; Kusmiyati, Kusmiyati; Merta, I Wayan (Jurnal Pijar Mipa, 2025)
Scientific Reasoning and Scientific Attitude are important aspects of scientific literacy for students to master because they are directly related to the development of science and technology. This study aims to analyze the effect of the Problem-Based Learning model on students' Scientific Reasoning and Scientific Attitude abilities. This type of research is classified as a quasi-experiment with a non-equivalent control group design. The study population consisted of 13 classes of the 10th grade of MAN 2 Mataram, from which two classes were selected as samples determined by purposive sampling techniques. Data were obtained by administering the Scientific Reasoning test and the Scientific Attitude questionnaire. Data analysis techniques include a comparison of average scores and the Mann-Whitney statistical test. The results showed that the experimental class obtained an average score of 75 points (formal), and the control class obtained a score of 72 points (transitional) on the Scientific Reasoning aspect. On the Scientific Attitude aspect, the experimental class obtained a score of 69 (High) and the control class obtained a score of 63 (Moderate). In addition, the Asympt. sig (2-tailed) value on the Scientific Reasoning aspect is greater than 0.05, which is 0.466, while on the Scientific Attitude aspect it is 0.003 or less than 0.05. Based on these findings, it can be concluded that although the Problem-Based Learning model has a significant effect on Students' Scientific Attitude Ability, its impact on Scientific Reasoning Ability is not statistically significant in the context of this study. This can be influenced by external factors that cannot be fully controlled in the research implementation process.